Akurasi Penerjemahan: Analisis Sinonim Kata Asal “Moderate” Hasil Terjemah Situs https://corpus.quran.com/ - Nursida, Ida; Yulyani, Rani Dewi; Raharja, Hatta (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
The discussion on synonymy in language has been a topic of debate for centuries, with conflicting views on the existence of synonyms. This study aims to analyze the meaning of the word "moderate" in Arabic and its component meanings, particularly in the context of Qur'anic translation. Through the analysis of translations of Qur'anic verses and word definitions in bilingual dictionaries, this study found significant differences in the understanding and interpretation of the word "moderate." The findings indicate that translation is not a static process but a dynamic one that depends on deep contextual understanding. The study also highlights the role of technology in translation research, but emphasizes its limitations in capturing the nuanced complexities of language. While technology can assist, the human ability to grasp contextual meaning remains essential in the translation process. In conclusion, this study provides new insights into the challenges of translating words with rich and complex meanings, while emphasizing the importance of a contextual approach that involves the human role. The main contribution of this research is to enrich the understanding of translation dynamics and the crucial role of translators in facilitating more accurate cross-linguistic communication.